(3eYGfi CHjGJ EUdGM GdefWbs - (3CHh eMeO jhSa Hf GdMSf Hf GdSjQGai GdfMhis; (3jYbhH Hf GSMGb, CHh jhSa, GHf GdScjJ,J (B224 (3g` s
(3ChdgG (B:s
(3JCedJ CQTOc Gddg cJGH EUdGM GdefWb aQCjJ GdThGgO ef GdTYQ ajg eNJdaI JRjO ai fSNI hJfbU aiCNQi hCfG HeTjFI Gddg CaSQ GdCHjGJ Ydi CcKQ eG CLO ai GdfSN s
(3BNQgG (B:s
(3EPG eG CfShG aRGYhG JMJ GdShQ HGdCYbGH hGdLRe JeJ eYGfi CHjGJ EUdGM GdefWb s
(3GdfSNI HgG MhGTs
(3efg fSN CNQi (B152 (3dZI , (B74 (3fMh , (B535 - 537 (3COHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B243 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B536s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B108s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs